By simplifying the given expression we will get that:
18*√8 = 36*√2
Here we start with:
18*√8
We can rewrite 18 as:
18 = √324
Replacing that in our expression we get:
√324*√8 = √(324*8) = √(2,592)
Now we need to rewrite 2,592 as the product of a square number and a non-square number (such that the non-square number is the smallest possible one).
If we divide 2,592 by 2, we get:
2592/2 = 1296
Then we can rewrite:
√2592 = √(2*1296) = √2*√1296 = √2*36
So this is the expression we wanted:
18*√8 = 36*√2
If you want to learn more about square roots, you can read:
https://brainly.com/question/8952483